Heyzine-Based Interactive E-Module to Improve Students' Understanding in Vocational High Schools - Vivi Pratiwi; Wulan Nawang Sari; Karimi (Economic Education Analysis Journal, 2025)
This study aims to provide an overview of the use of Heyzine-based interactive e-modules to enhance students’ understanding in Vocational High Schools (SMKs). A quantitative descriptive approach employing a case study method was applied in this research. The participants consisted of 20 VHS students selected through a purposive sampling technique. Data were collected using multiple-choice tests, interviews, and observations. The findings revealed that the use of interactive e-modules in learning activities significantly improved students’ average learning outcomes from 55 to 89.5. This improvement reflects the students’ enhanced ability to solve problems related to service company materials. Moreover, the integration of interactive e-modules fostered more engaging and active learning experiences, aligning with the principles of the Kurikulum Merdeka, which emphasizes student-centered and enjoyable learning. Overall, the results indicate that interactive e-modules are effective in improving students’ understanding and learning outcomes. These findings offer valuable insights for the development and implementation of innovative, technology-enhanced learning media designed to enhance instructional quality and learning effectiveness in SMKs.